Dispositional mindfulness and relapse vulnerability as mediated by self-efficacy among persons in recovery from substance use disorders (SUDs). - Galacgac, N. B.
The study sought to explain the potential mechanism by which dispositional mindfulness influences relapse vulnerability through the function of self-efficacy among persons in recovery from Substance Use Disorders (SUDs). Data were collected from residential/in-patient clients (N=206) admitted in both private and government funded drug rehabilitation centers. Results of the mediation analysis suggest that the naturally-occurring trait of being fully attentive to present experiences allows people recovering from SUDs to attain a state of awareness, thereby accessing functional perceptions about the self, such as the perceived capacity to accomplish tasks and overcome difficulties. At the face of high-risk situations that may incite relapse, dispositional mindfulness contributes partially to this sense of command or mastery consequently allowing individuals to cope constructively, as opposed to the automatic response of reverting to substance use to diminish distress or regain control over stressful experiences. The findings provided implications for relapse prevention and the utility of mindfulness-based interventions for SUDs.